(untitled) - Ellis, Harold (London, 2001)
This book provides a fascinating and interesting introduction to the subject for anyone with an interest in it. It illustrates some of the key advances in surgery from primitive techniques such as trepanning, through some of the gruesome but occasionally successful methods employed by the ancient civilisations, the increasingly sophisticated techniques of the Greeks and Romans, the advances of the Dark Ages and the Renaissance and on to the early pioneers of anaesthesia and antisepsis such as Morton, Lister and Pasteur.
Keywords: Surgery,Phẫu thuật; Lịch sử; History